Radiolink Microwave Sebagai Infrastruktur Telekomunikasi Sistem SCADA - Suhardhika Sih Sudewanto (Sekolah Tinggi Teknik - PLN, 2020)
Expansion of the electrical network and substation makes a demand of the telecommunication channel for SCADA system is high. Telecommunication infrastructure which operates based on Power Line Carrier (PLC) can not provide adequate supply. Therefore, It needs new media to fulfill the demands of the telecommunication channel for SCADA System. Selection methods will be done by comparing technical and non-technical aspects of various telecommunication media that operates in the PLN network. One of suitable media is microwave radiolink. With high capacity and bandwidth, microwave radiolink can be the backbone of SCADA System